A Review of Research Work done in Bihar on Crop and Grassland Management - Singh, R.D.; Chatterjee, B.N. (Journal of Soil and Water Conservation, 2022)
Grazing and fodder resources of India is inadequate to meet the needs of its live-stock population. These resources not only contri- bute to the improvement in the plane of nutrition of the live-stock and consequently its human population but also play an important role in the improvement of soil fertility and in the conservation of soil and water by providing a protective plant cover. Increased production of both live-stock and agricultural pro- duct goes closely hand in hand,with high profitability per acre and per unit of labour. In India the grass and fodder crop is not at present being farmed at as high a level as that of other arable crops. This is not due to the negligence of our farmers towards livestock but mainly due to population pressure and small fragmented holdings which has resulted in the prevailing subsistence farming. Efforts, ther- fore will have to be made mainly on improving the existing fodder resources of country and, if possible, to exploit the so called waste submarginal lands to increase the fodder °resources as well as to improve the fertility status of these lands. Suitable fodder crops to fit in the general cropping pattern of the country will also have to be evolved.